ANALISIS SEKTOR UNGGULAN UNTUK MEWUJUDKAN KOTA MAGELANG YANG MAJU DAN BERDAYA SAING - Febrianti, Erika; Sarfiah, Sudati Nur (Badan Perencanaan Pembangunan, Riset dan Inovasi Daerah Kota Magelang, 2022)
Identifying leading sectors is important, especially in determining future economic development strategies. Therefore, this study was conducted in order to improve the economic competitiveness of Magelang City as the vision that stated in RPJPD Magelang City 2005-2025 with redaction “Magelang as a service city that cultured, advanced and competitive in civil society”. The methods used is a combined analyst of static and dynamic Location Quotient (LQ), Shift-share, Growth Ratio Model (MRP), Overlay, and Klasssen Typology. The results showed that 4 (four) sectors are classified into advanced and rapidly growing sectors: electricity, gas and water supply; transportation and warehousing; Mandatory government administration, defense, and compulsory social security; and Educational services. Economic development strategies to improve the economic competitiveness of Magelang city can bedone in short, medium, and long term.